From Mild Encephalitis Hypothesis to Autoimmune Psychosis - and remaining challenges - K. Bechter (European Psychiatry, 2022)
Introduction The mild encephalitis (ME) hypothesis of severe mental disorders, ME to be caused by infections, autoimmunity , toxicity and trauma ( Bechter 2001, updated Bechter 2013), is now emergingly supported from neuroimaging and CSF and postmorten findings.